A parent-oriented alcohol prevention program "Effekt" had no impact on adolescents' alcohol use: Findings from a cluster-randomized controlled trial in Estonia. (1st January 2019) - Tael-Öeren, Mariliis; Naughton, Felix; Sutton, Stephen
Highlights: Previous studies on prevention programme's "Effekt" effectiveness show mixed results. The programme "Effekt" was implemented in Estonia in 2012–2015 in 34 schools. The content was modified – additional topics and increased interaction with parents. Parental alcohol-related attitudes at the intervention schools became more restrictive. The programme did not succeed in delaying or reducing adolescents' alcohol use. Abstract: Aim: To evaluate the effectiveness of a universal parent-oriented alcohol prevention program ("Effekt") in Estonia. The main objective of the program was to delay and reduce adolescents' alcohol consumption by maintaining parental restrictive attitudes towards adolescents' alcohol use over time. Methods: A matched-pair cluster randomized controlled trial with a three-year assessment period (baseline (T1), 18-months (T2) and 30-months (T3) follow-ups) was undertaken in 2012–2015 among 985 fifth grade adolescents and 790 parents in sixty-six schools (34 intervention, 32 control). The primary outcome measure was adolescents' alcohol use initiation. Secondary outcome measures were lifetime drunkenness and alcohol use in the past year. Intermediate outcomes were restrictive parental attitudes towards adolescents' alcohol use reported by parents and perceived restrictive parental attitudes and parental alcohol supply reported by adolescents. Results: There were no significant differences in adolescents' alcohol use initiation, lifetime drunkenness, alcohol use in the past year, parental alcohol supply, and adolescent's perception of parental restrictive attitudes between intervention and control school participants at T2 and T3. There were significant differences in parental attitudes – the odds of having restrictive attitudes were 2.05 (95% confidence interval (CI) = 1.32–3.17) times higher at T2 and 1.92 (95% CI = 1.31–2.83) times higher at T3 in the intervention group than in the control group. Conclusions: The Estonian version of the "Effekt" program had a positive effect on parental attitudes, but it did not succeed in delaying or reducing adolescents' alcohol consumption.